PENGARUH MINAT KERJA DAN PRESTASI BELAJAR TERHADAP KESIAPAN BEKERJA DI LEMBAGA KEUANGAN. (MAHASISWA AKUNTANSI STIE WIDYA WIWAHA) - Kundala, Manendha Maganitri; Khoirunnisa Cahya Firdarini (PRIMA EKONOMIKA, 2025)
ABSTRACT This study aims to determine the effect of interest on readiness to work in financial institutions and the effect of learning achievement on readiness to work in financial institutions. The method used is quantitative research with the object of research being accounting students of STIE Widya Wiwaha obtained 40 respondents. The results of the study of the work interest variable (X1) have a positive impact on readiness to work in financial institutions. With a calculated T value of 4.298> T table 2.021, the significance value of the work interest variable (X1) is 0.000 <0.05. From the results above, it states that H1 is accepted by the research data on work interest on readiness to work in financial institutions (Accounting Students of STIE Widya Wiwaha). The Learning Achievement variable (X1) has a positive and significant impact on readiness to work in financial institutions. With a calculated T value of 2.235 > T table 2.021, the significance value of the Learning Achievement variable (X1) is 0.000 <0.05. So it can be concluded that the results of the learning achievement variable (X1) have a positive and significant impact on readiness to work in financial institutions. From the results above, it states that H2 is accepted by the research data on learning achievement on readiness to work in financial institutions (Accounting Students of STIE Widya Wiwaha). ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh minat terhadap kesiapan bekerja di lembaga keuangan dan pengaruh prestasi belajar terhadap kesiapan bekerja di lembaga keuangan. Metode yang digunakan penelitian kuantitatif dengan objek penelitian mahasiswa akuntansi STIE Widya Wiwaha diperoleh 40 responden. Hasil penelitian variabel minat kerja (X1) membawa dampak positif terhadap kesiapan bekerja di lembaga keuangan. Dengan nilai T hitung 4.298 > T tabel 2.021 nilai signifikansi variabel minat kerja (X1) senilai 0,000 < 0,05. Dari hasil diatas menyatakan H1 diterima oleh data penelitian minat kerja terhadap kesiapan bekerja di lembaga keuangan (Mahasiswa Akuntansi STIE Widya Wiwaha). Variabel Prestasi Belajar (X1) membawa dampak positif dengan signifikan terhadap kesiapan bekerja di lembaga keuangan. Dengan nilai T hitung 2.235 > T tabel 2.021 nilai signifikansi variabel Prestasi Belajar (X1) senilai 0,000 < 0,05. Sehingga dapat ditarik kesimpulan hasil dari variabel prestasi belajar (X1) membawa dampak positif dan signifikan terhadap kesiapan bekerja di lembaga keuangan. Dari hasil diatas menyatakan H2 diterima oleh data penelitian prestasi belajar terhadap kesiapan bekerja di lembaga keuangan (Mahasiswa Akuntansi STIE Widya Wiwaha).